1997
DOI: 10.1182/blood.v89.4.1133
|View full text |Cite
|
Sign up to set email alerts
|

Use of Leukemic Dendritic Cells for the Generation of Antileukemic Cellular Cytotoxicity Against Philadelphia Chromosome-Positive Chronic Myelogenous Leukemia

Abstract: The success of adoptive immunotherapy for the treatment of leukemia depends on the generation of T cells that can specifically react with malignant cells. Dendritic cells (DCs) are important antigen-presenting cells in the development of antileukemic T-cell responses. In this study, we generated DCs from peripheral blood cells of patients with chronic myelogenous leukemia (CML). CML cells incubated concurrently with granulocyte-macrophage colony-stimulating factor, interleukin-4, and tumor necrosis factor-α in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(67 citation statements)
references
References 18 publications
3
64
0
Order By: Relevance
“…28) In agreement with the present findings, the DCs generated from the CML progenitors have been shown to carry t(9;22), which suggests they are leukemic in origin. 13,29) In addition, the DR + CD86 + phenotype and the morphology of these mature leukemic DCs are similar to those of typical mature DCs. 13) In this in vitro study, we showed that leukemic DCs can take up exogenous particles, such as latex beads, and KLH protein.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…28) In agreement with the present findings, the DCs generated from the CML progenitors have been shown to carry t(9;22), which suggests they are leukemic in origin. 13,29) In addition, the DR + CD86 + phenotype and the morphology of these mature leukemic DCs are similar to those of typical mature DCs. 13) In this in vitro study, we showed that leukemic DCs can take up exogenous particles, such as latex beads, and KLH protein.…”
Section: Discussionmentioning
confidence: 58%
“…13,29) In addition, the DR + CD86 + phenotype and the morphology of these mature leukemic DCs are similar to those of typical mature DCs. 13) In this in vitro study, we showed that leukemic DCs can take up exogenous particles, such as latex beads, and KLH protein. They can also function as potent accessory cells in the proliferation of KLH antigen-specific CD4 + T cells, as well as in stimulating an allo-T cell response.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…70 Myeloid progenitors obtained from patients with AML differentiated to enhanced antigenpresenting cells when treated in vitro with GM-CSF, TNF, IL-4, CD40 ligand, Flt3, or SCF. 71 Likewise, others have reported similar results after GM-CSF, TNF, and IL-4 culture of cells obtained from patients with AML and CML; 72,73 and Coleman et al reported the restoration of costimulatory molecules on GM-CSF and IL-4-incubated T-cells obtained from patients with CML. 74 In a series of interrelated trials reported by Bedi et al and Jones et al, CML progenitor cells were eliminated preferentially from culture through terminal differentiation in the presence of hematopoietic growth factors.…”
Section: Hematologic Malignanciesmentioning
confidence: 67%